USA AND WESTERN EUROPEAN SANCTIONS POLICY WITH RESPECT TO RUSSIA - I. Aksenov (Вестник университета, 2019)
The implementation of the sanctions policy of the United States and Western Europe in relation to the Russian Federation has been analyzed. The objectives of the USA and European Union sanctions policies have been identified. The study has been based on the principles of a three-level classification of sanctions aimed at destabilizing the economy of the Russian Federation. Sectors of the economy and companies have been identified, that, have become objects of sanctions policy and have suffered more from USA and European Union sanctions. The role of sanctions as a toolkit, which can influence the political and economic balance of power in the world, has been defined. The opinion of representatives of business of foreign countries on the formation of anti-Russian sanctions has been reflected within the article. The features of the implementation of the sanctions policy in the digital block and cyberspace have been noted.